Association between glycosylated hemoglobin and blood lead: A cross-sectional study. - Wei Wang; Pengfei Jing; Hongsen Zhao; Jibo Cheng; Zewei Yang; Fan He; Shuquan Lv (PLoS ONE)
Background Diabetes is the most common chronic metabolic disease, affecting many people's health. Previous studies have shown a close relationship between trace elements and metabolic diseases. This study investigated the interrelationship between glycosylated hemoglobin (HbA1c) and blood lead (BPb) in adults. Method This research was carried out involving 12,049 eligible individuals aged 20 years or above from the National Health and Nutrition Examination Survey (NHANES) spanning from 2011 to 2020. Weighted linear regression models and smoothed curve fitting were employed to investigate the association between HbA1c and blood lead. Analyses were stratified based on age, sex, race, and body mass index, and threshold effects were explored using two-stage segmented linear regression models. Result Among all 12049 participants, through comprehensive adjustment of the model, this study discovered a negative association between HbA1c and blood lead. In addition, when stratified by sex, age, race, and BMI status in subgroup analysis in this study, this correlation still had specific statistical significance. In performing subgroup analyses, we found that the relationship between HbA1c and blood lead may yield distinct outcomes arise from gender disparities. In women, a significant U-shaped association exists between HbA1c and BPb. At approximately 6.6% of HbA1c value, the relationship between the two shifts from negative to positive. Conclusion This investigation proposes a "U" form association between HbA1c and BPb in American adults.